A Concise Total Synthesis of (+)-Waihoensene Guided by Quaternary Center Analysis - Peng, Cheng (Angew Chem Int Ed Engl, 2020)
The four contiguous all-carbon quaternary centers of waihoensene, coupled with the absence of any traditional reactive functional groups other than a single alkene, renders it a particularly challenging synthetic target among angular triquinane natural products. Here, we show that its polycyclic frame can be assembled concisely by using a strategically selected quaternary center to guide the formation of the other three through judiciously selected C–C bond formation reactions. Those events, which included a unique Conia-ene cyclization and a challenging Pauson–Khand reaction, afforded a 17-step synthesis of the molecule in enantioenriched form.